Stability of hematological analytes during 48 hours storage at three temperatures using Cell-Dyn hematology analyzer: Stability of hematological analytes - Ünallı Özmen, Sevda (Journal of Medical Biochemistry, 2020)
Background: The complete blood count (CBC) with differential leukocyte count (DLC) is one of the most common tests requested by physicians. The results of this test are affected by storage temperature and time of incubation. This study was designed to evaluate the stability of hematologic parameters in blood specimens stored for 48 hours at three temperatures.Methods: K2 EDTA- blood was collected from 22 apparently healthy adults. The CBC was performed using Cell-Dyn 3700 hematology analyzer (Abbott Diagnostics, IL, USA)  immediately; 0 Time Point and at 4, 8, 12, 16, 20, 24 and 48 h after storage at 4°C, 10°C or 23°C. Changes in values of CBC parameters from the 0 Time Point were determined and reported as % of the initial value. Statistical comparisons were made using the paired-t test and the repeated measures ANOVA. Results: RBC, PLT, Hb and MCH were found stable during 48 h storage at 4°C, 10°C or 23°C. HCT and MCV increased, while WBC decreased significantly at 48 h when stored at 23°C. LYM, NEU, EOS and BASO values showed significant differences after 12 h of storage at 23°C. WBC, HCT, MCV, MCHC, RDW, NEU, MONO, BASO and EOS were stable for 48 h if blood samples were stored at 4°C or 10°C.Conclusions: RBC, PLT, Hb and MCH are the only suitable parameters without refrigeration during 24 h storage. When CBC and DLC are performed, 4°C can be recommended as the most suitable storage temperature for 12 h storage.